Tahapan Pembuatan E-Booklet Sebagai Media Informasi Objek Wisata Kedung Kandang di Desa Wisata Nglanggeran - Prananta, Rebecha; Safitri, Nurul Qomariah Laili (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
Nglanggeran Tourism Village has several leading tourist objects, one of which is Kedung Kandang. The Kedung Kandang area presents an epic blend of natural beauty and modern accommodation, namely glamping. Some of the supporting facilities at Kedung Kandang have not been able to bring in many visitors, this is due to several factors, one of which is the lack of information and promotional media. One of the information media that can be used is e-booklets. The Kedung Kandang e-booklet displays some information such as Kedung Kandang Waterfall, glamping, flora and fauna, existing facilities and packages that can be chosen when visiting Kedung Kandang. To apply the Kedung Kandang e-booklet as an information medium, there are several means that are used, namely through the link in Kedung Kandang's Instagram bio and the QR code that can be found at the entrance to the Nglanggeran Purba Volcano. The purpose of this research is to describe the stages of making the Kedung Kandang e-booklet as a tourist information medium and to describe the material displayed in the Kedung Kandang e-booklet. Data collection methods used are observation, interviews and literature study. The results of this study are: (1) the stages of making the Kedung Kandang e-booklet as a tourist information medium; (2) material displayed in the Kedung Kandang e-booklet.